2016
DOI: 10.1080/00498254.2016.1193264
|View full text |Cite
|
Sign up to set email alerts
|

Structure- and isoform-specific glucuronidation of six curcumin analogs

Abstract: 1. In the present study, we aimed to characterize the glucuronidation of six curcumin analogs (i.e. RAO-3, RAO-8, RAO-9, RAO-18, RAO-19, and RAO-23) derived from galangal using human liver microsomes (HLM) and twelve expressed UGT enzymes. 2. Formation of glucuronide was confirmed using high-resolution mass spectrometry. Single glucuronide metabolite was generated from each of six curcumin analogs. The fragmentation patterns were analyzed and were found to differ significantly between alcoholic and phenolic gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The commercial enzyme is not inactive. It was previously reported to catalyze glucuronidation of several compounds, such as curcuminoids 32 and curcumin analogues, 33 but no comparison to the activity of the native intestinal UGT1A10 toward these compounds was presented. In the present study we have shown that commercial UGT1A10 is able to catalyze the glucuronidation of 4-MU, SN-38, and estradiol (Figures 2 and 4).…”
Section: ■ Discussionmentioning
confidence: 99%
“…The commercial enzyme is not inactive. It was previously reported to catalyze glucuronidation of several compounds, such as curcuminoids 32 and curcumin analogues, 33 but no comparison to the activity of the native intestinal UGT1A10 toward these compounds was presented. In the present study we have shown that commercial UGT1A10 is able to catalyze the glucuronidation of 4-MU, SN-38, and estradiol (Figures 2 and 4).…”
Section: ■ Discussionmentioning
confidence: 99%
“…It is well‐accepted that glucuronidation is important metabolic clearance pathway because the glucuronide is usually pharmacologically inactive and rapidly eliminated from the body due to its highly polar nature . Previous studies have proved that numerous UGT1As and 2Bs enzymes participated in the glucuronidation of curcumin analogs . Traditionally, the glucuronides were formed by UGT enzymes in cell, and the glucuronides were further transferred from intracellular to extracellular by efflux transporters .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the widespread use of CUR in the Southeastern Asians, such herb-drug interactions seem to be very important. COG, generated in enterocytes and hepatocytes by UGTs (Lu, et al, 2017), is transported to the blood, in turn, by the basolateral membrane transporter MRP3 of enterocytes and the sinusoidal plasma membrane transporter MRP3 of hepatocytes, consequently leading to a dramatic increase in its systemic exposure. As summarized in Table 1, compared to WT mice, Mrp3 KO mice exhibited significantly declined systemic exposure of COG (reflective of decreased AUC and Cmax) and extended elimination process (increased t1/2), consistent with expected results.…”
Section: Discussionmentioning
confidence: 99%
“…In the gut mucosa and epithelial cells, ingested CUR is converted to COG by the intestinal UGTs (i.e., UGT1A7, UGT1A8, and UGT1A10) (Lu, et al, 2017), which is transported, in turn, to the blood via Mrp3 expressed on the basolateral membrane of enterocytes, or back to the gut lumen via the efflux transporters (such as Mrp2 and Bcrp) expressed on the apical side of enterocytes, where the enterohepatic circulation of COG would occur (Bangphumi, et al, 2016). Furthermore, COG formed in hepatocytes is transported to the blood via Mrp3 expressed on the sinusoidal side of hepatocytes, and to the bile via Mrp2 and Bcrp on the apical side of hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation